Secretion of paracrine factors enabling expansion of cumulus cells is developmentally regulated in pig oocytes - Nagyová, E; Vanderhyden, B C; Procházka, R (Biology of reproduction, 2000)
To demonstrate secretion of cumulus expansion-enabling factor (CEEF) by porcine oocytes, we used an interspecies testing system. Porcine oocytes were used to condition culture medium, and the presence of CEEF was tested using mouse oocytectomized complexes (OOX), which require CEEF for expansion. Follicle-stimulating hormone-stimulated expansion and synthesis of hyaluronic acid (HA) by mouse OOX were assessed after 18 h of culture in media conditioned by porcine oocytes: 1) at different stages of maturation and 2) in which maturation was inhibited with a specific inhibitor of cdk-kinases, butyrolactone I. Fully grown (GV-germinal vesicle), late-diakinesis (LD), metaphase I (MI), and metaphase II (MII) oocytes were prepared by culture of oocyte-cumulus complexes (OCC) for 0, 22, 27, and 42 h, respectively. To block GV breakdown, porcine oocytes were cultured for 27 h in medium supplemented with butyrolactone I (50 microM). Medium conditioned by oocytes in GV, LD, and after butyrolactone I block allowed full expansion of >90% of mouse OOX, whereas oocytes in MI and MII caused disintegration of mouse OOX without cumulus mucification. To measure synthesis of HA by cumulus cells, 25 mouse OOX were cultured in the conditioned media in the presence of 2.5 microCi of D-[6-(3)H]glucosamine hydrochloride. After 18 h, incorporation of the [(3)H]glucosamine into HA was determined either in complexes (retained HA) or in medium plus complexes (total HA). Total HA accumulation by mouse OOX was not different from that of intact OCC. However, oocytes in GV, LD, and after butyrolactone I treatment enabled mouse OOX to retain significantly more HA within the complex than oocytes in MI and MII. The results indicate that secretion of factors that promote the retention of HA within the complex is developmentally regulated during oocyte maturation.
Keywords: gama-butyrolakton; Animals; Paracrine Communication; Female; Meiosis; parakrinní signalizace; kultivační média speciální; ženské pohlaví; Follicle Stimulating Hormone; meióza; Oocytes; Enzyme Inhibitors; ovariální folikul; Mice; oocyty; prasata; Culture Media, Conditioned; kyselina hyaluronová; kultivované buňky; myši; Cyclin-Dependent Kinases; Hyaluronic Acid; cyklin B; Cells, Cultured; Swine; 4-Butyrolactone; Cyclin B; inhibitory enzymů; Mice, Inbred ICR; myši inbrední ICR; histony; Histones; zvířata; Ovarian Follicle; folikuly stimulující hormon; cyklin-dependentní kinasy